Система регулювання температури електротермічного двигуна - Ахмад, Д. Х. (ХНУРЕ, 2021)
In this work, a model of a system for regulating the temperature inside the thermal chamber of an electrothermal motor by current in a resistive heater, which is made of a carbon composite material was proposed. As a feedback element, it is proposed to use an integral estimate in a cameral atom, which is based on a change in the resistance of a carbon composite material with increasing temperature.
Keywords: електротермічний двигун; регулювання температури